ANALISIS FAKTOR-FAKTOR DETERMINASI PASAR BENIH KELAPA SAWIT DI INDONESIA - Tony Liwang; Arief Daryanto; E. Gumbira-Said; Nunung Nuryartono (Manajemen Bisnis, 2011)
* Plant Production and Biotechnology Division, PT SMART Tbk., Jakarta** Manajemen dan Bisnis, Institut Pertanian Bogor, Bogor.Email : toniyLiwang@smart-tbk.comABSTRACTThe development of oil palm (Elaeis guinensis Jacq.) industry in Indonesia was very fast,especially within the last decade. This rapid development was in line with the increasing of land usedfor oil palm plantation and the availability of oil palm hybrid seeds. Until 2009 the demand of oilpalm certified hybrid seeds was beyond its supply which has resulted into the usage of the illegal oilpalm seeds with low quality. One of the strategies to solve the shortage of certified hybrid seeds wasto increase the number of seed producer in Indonesia, so that since 2009 the oil palm seeds produceddomestically was over supplied. However, the usage of illegal oil palm seeds was still taking place.Therefore, this research was designed to analysis the determinant factors of oil palm seeds market inIndonesia based on consumer's demography profile, purpose and frequency seed purchase,costumer satisfaction level and seed compatibility. This research was based on the survey taken fromthe respondents in the regency of Siak, Kampar and Rokan Hulu, province of Riau. Selection of therespondents was used the convenience sampling method and later on by judgmental sampling. Slovinmethod was used to determine number of respondent. Data was analyzed using descriptive analysisand ordinal logistic regression analysis. The results of data analysis shown that the amount of soldseeds was depend on demographic factors, i.e. gender, education level, activity and consumer statusin company, but not age of consumers. The purpose and frequency to purchase the oil palm seedswere negatively correlated to the number of sold seeds. Moreover, the level of customer satisfactionhas significant effect on the number of sold seeds.Keyword: consumer, seed, oil palm, determinant factors, analysis of ordinal logistic.